Effects of levomilnacipran extended-release on motivation/energy and functioning in adults with major depressive disorder - Thase, Michael E. (Int Clin Psychopharmacol, 2016)
The objective of this post-hoc analysis was to investigate the relationship between motivation/energy and functional impairment in patients with major depressive disorder (MDD). Data were taken from a phase 3 trial of levomilnacipran extended-release (ER) in adults with MDD (NCT01034462; N=429) that used the 18-item Motivation and Energy Inventory (MEI) to assess motivation/energy. Two subgroups with lower and higher motivation/energy were defined using baseline MEI total scores (≤28 and >28, respectively). Change from baseline in the Sheehan Disability Scale (SDS) total score was analyzed in the intent-to-treat (ITT) population and both subgroups. Path analyses were carried out in the ITT population and a lower MEI subgroup to assess the direct and indirect effects of levomilnacipran ER on SDS total score change. In the ITT population and the lower MEI subgroup, significant differences were found between levomilnacipran ER and placebo for changes in the SDS total score (−2.6 and −3.9, both P<0.01), but not in the higher MEI subgroup. The indirect effect of levomilnacipran ER on SDS total score improvement, as mediated by MEI total score change, was 79.9% in the lower MEI subgroup and 67.2% in the ITT population. Levomilnacipran ER was previously shown to improve motivation/energy in adults with MDD. The current analysis indicates that improvements in functional impairment were considerably mediated by improvements in motivation/energy, particularly in patients with lower motivation/energy at baseline.